The endothelial activation and stress index is a potential prognostic indicator for patients with acute pancreatitis managed in the intensive care unit: a retrospective study - Wang, Jianjun; Chen, Xi; Qin, Chuan; Zeng, Xintao; Du, Xiaobo; Wang, Decai (Frontiers in Medicine, 2024)
The endothelial activation and stress index (EASIX) serves as a dependable and efficient surrogate marker for endothelial dysfunction, which plays an essential role in the pathophysiology of acute pancreatitis (AP). Hence, we investigated the prognostic value of EASIX in AP.This was a retrospective study, using patient information obtained from the Medical Information Market for Intensive Care-IV (MIMIC-IV) database. EASIX was calculated using lactate dehydrogenase, serum creatinine, and platelet counts obtained during the first measurement within 24 hours of admission. Patients were grouped into three cohorts based on log2-transformed EASIX. The main endpoint of the study was 28-day all-cause mortality (ACM) in AP patients, with the secondary endpoint being 90-day ACM. The relationship between EASIX and prognosis in patients with AP was evaluated using Cox proportional hazards models, Kaplan-Meier curves, restricted cubic spline 2 (RCS) curves, and subgroup analyses. Receiver operating characteristic (ROC) curves were constructed to evaluate the predictive performance of EASIX compared to other indicators.The study cohort comprised 620 patients in total. Multivariate Cox proportional hazards analysis indicated that an increased log2 (EASIX) was linked to a higher risk of 28-day ACM in AP